Antibacterial Effect of Averrhoa bilimbi Extract on Lactobacillus acidophilus ATCC 4356 - Sovira, Gita Dwi Jiwanda; Rahmawati, Fitri; Nofika, Reni; Fitri, Haria; Khairani Aulia, Rahmi; Kurnia, Puji; Ladyventini, Yona (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Introduction: Lactobacillus acidophilus is one of the dominant bacteria that plays a significant role in the development of dental caries. This bacterium produces extracellular polysaccharides that facilitate bacterial adhesion to dental plaque. One of the approaches to preventing dental caries is the use of antibacterial agents to inhibit bacterial growth in dental plaque. Averrhoa bilimbi (cucumber tree fruit) leaves have the potential to act as antibacterial agents due to the presence of active compounds that can inhibit bacterial growth. Aim: To determine the effect of Averrhoa bilimbi (cucumber tree fruit) leaf extract on inhibiting the growth of Lactobacillus acidophilus ATCC 4356. Methods: This study was an experimental laboratory with a post-test only control group design. The concentrations of Averrhoa bilimbi leaf extract used were 6.25%, 12.5%, 25%, and 50%, and a negative control of aquadest (sterile water). Results: The analysis with One Way ANNOVA showed p-value < 0.05, indicating a significant effect of Averrhoa bilimbi leaf extract in inhibiting the growth of Lactobacillus acidophilus ATCC 4356. Conclusion: Averrhoa bilimbi (cucumber tree fruit) leaf extract has an effect on inhibiting the growth of Lactobacillus acidophilus ATCC 4356. These findings suggest the potential of Averrhoa bilimbi leaf extract as a natural antibacterial agent